Biofilm formation in trimethoprim/sulfamethoxazole-susceptible and trimethoprim/sulfamethoxazole-resistant uropathogenic Escherichia coli - Nitis Smanthong; Ratree Tavichakorntrakool; Phitsamai Saisud; Vitoon Prasongwatana; Pipat Sribenjalux; Aroonlug Lulitanond; Orathai Tunkamnerdthai; Chaisiri Wongkham; Patcharee Boonsiri (Asian Pacific Journal of Tropical Biomedicine, 2015)
Objective: To compare biofilm formation in trimethoprim/sulfamethoxazole (SXT)-susceptible Escherichia coli (E. coli) (SSEC) and SXT-resistant E. coli (SREC) isolated from patients with urinary tract infections, and study the motile ability and physical characteristics of the isolates. Methods: A total of 74 E. coli isolates were tested for antimicrobial susceptibility with the disc diffusion assay. Based on the SXT-susceptibility test, the E. coli isolates were divided into SSEC (N = 30) and SREC (N = 44) groups. All E. coli isolates were examined for motile ability by using a motility test medium, and for checking biofilm formation a scanning electron microscope was used. Bacterial colony size was measured with a vernier caliper and bacterial cell length was measured under a light microscope. The bacterial growth rate was studied by plotting the cell growth (absorbance) versus the incubation time. Results: The frequencies of non-motility and biofilm formation in the SREC group were significantly higher than that in the SSEC group (P < 0.01). The SREC bacterial cell length was shorter than that in the SSEC group [(1.35 ± 0.05) vs. (1.53 ± 0.05) μm, P < 0.05)], whereas the bacterial colony size and mid-log phase of the growth curve were not significantly different. Conclusions: The present study indicated that biofilm formation and phenotypic change of uropathogenic E. coli can be attributed to the mechanism of E. coli SXT resistance.